FINITE ELEMENT ANALYSIS OF POST-TENSIONED CONCRETE BOX GIRDERS (Journal of Engineering, 2007)
The behavior of prestressed concrete box-girder bridges has been studied under short term loading.The 20-noded isoparametric three-dimensional brick elements have been used to model the concretein the box-girder with its two cantilever flanges. The reinforcing bars are idealized as axialmembers embedded within the brick elements. The behavior of concrete in compression wassimulated by an elastic-plastic work hardening model followed by a perfectly plastic response,which is terminated at the onset of crushing. In tension, a smeared crack model with fixedorthogonal cracks is used with the inclusion of models for the retained post-cracking stress andreduced shear modulus. The prestressing forces in the tendons are transformed into equivalent nodalforces and by Lin's method. The contribution of the prestressing tendon stiffness to the globalstiffness matrix is considered by treating the tendon as axial member embedded within the brickelement. Two types of short-term prestress losses are considered in this study. The bond-slipphenomenon at concrete-tendon is considered by reducing the tendon axial stiffness. Severalexamples of prestressed concrete box girders are analyzed and compared with availableexperimental and theoretical studies in order to demonstrate the validity and efficiency of theproposed method. Good agreements between the results are obtained.